Building a service delivery infrastructure (O'Reilly Media, 2019)
"Teams considering adoption of service-based or microservice architectures have a wealth of information to consult on the organization and design of application software, the benefits of these architectural approaches, and general considerations for the prerequisites. Even if you're not ready to adopt a microservices architecture, you still want the benefits of rapidly deployable, highly automated infrastructure that enables rapid delivery of new features and services. What can you do to build an infrastructure that supports such mythical delivery? Delivery infrastructure refers to a set of products and capabilities that serve the needs of product developers and operations teams. Paula Paul and Rosemary Wang offer a deeper look at an approach to building the necessary delivery infrastructure to support a distributed service or microservice architecture. You'll explore delivery infrastructure products and their capabilities as well as related aspects of change friction for core compute, observability, delivery pipelines, security, persistence, and more."--Resource description page